Promoting urban water bodies as a potential strategy to improve urban thermal environment - Syafii, Nedyomukti (Geographica Pannonica, 2021)
Cities are found warmer than in nearby surrounding rural areas due to change in surface properties and lack of evaporation, indicated as urban heat island (UHI). Water bodies, on the other hand, have been known to generate a positive impact on the urban microclimate by maintaining a cooler thermal environment. Although researches have been conducted many experiments and measurements to illustrate its potential benefits, most of them are studied in terms of its capacity to ameliorate the air temperature. In this paper, the benefits of urban water bodies are evaluated regarding their radiation properties. With the main objective to find a novel approach to take advantage of urban water bodies’ abilities to improve the urban thermal environment, a series of field measurements have been conducted inside an urban scale model. Generally, the measured long-wave and short-wave radiation within the urban canyon shows that bodies of water tend to absorbed and store more heat, which in turn generate lower surface temperature as compared to those flat concrete surface.